2007
DOI: 10.1051/vetres:2007011
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study on feed risk factors for BSE cases born after the feed ban in France

Abstract: -In France, after the ban on meat and bone meal (MBM) in cattle feeding in June 1990, cases of Bovine Spongiform Encephalopathy (BSE) have continued to be detected in bovines born after that ban (called BAB cases). A case-control study was therefore carried out to determine the way these cases were contaminated. A multivariate conditional model was built adjusting for the production type of the animals and taking into account the herd size. The results confirmed that feeding cattle with proprietary concentrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…Our results agree with those of the case-control study (23), which did not provide evidence that use of mineral and vitamin compounds affect risk for BSE; the authors considered that the implication of animal DCP as a source of BSE, if it existed, should have been marginal. In contrast, a risk analysis by the European Food Safety Agency (www.efsa.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results agree with those of the case-control study (23), which did not provide evidence that use of mineral and vitamin compounds affect risk for BSE; the authors considered that the implication of animal DCP as a source of BSE, if it existed, should have been marginal. In contrast, a risk analysis by the European Food Safety Agency (www.efsa.…”
Section: Discussionsupporting
confidence: 86%
“…This result favors the effect of cross-contamination of cattle feed with MBM-containing feed for monogastric species as a source of BSE for cattle born after the ban of MBM. A recent epidemiologic study in France (23) clearly showed that cattle that consumed feed from factories were at risk for BSE after the feed ban; it also showed that mixed farms were at a higher risk for BSE, which indicates that cross-contamination has possibly occurred on farms (by feeding monogastric-species feed to bovines). These fi ndings are in agreement with our results; both studies complement each other and raise the question of effectiveness of the ban that was initially restricted to bovines and belatedly extended to other species to reduce cross-contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence on the BAB cases arising from the feedborne source has been provided by Sheridan et al [57], where a spatial relationship between feed-producers and BSE cases was found. Recently, a case-control study [42] evidenced the use of feed from feedstuff factories fed to young cattle as well as the existence of poultry operation in the farm, if using compound feed, as risk factors for BSE, and thus reinforced the role of compound feed in the risk of BSE.…”
Section: Routes Of Infectionmentioning
confidence: 99%
“…In Germany, milk replacers could legally contain animal-derived fats until 2000, and it is possible that either infectious material survived the rendering process or that infectious material entered milk replacers through the use of unrefined fats, which were used in milk replacers in Germany [43]. Pottgiesser et al [52] have also shown a possible association of the feeding of milk replacers with BSE infection in the Schleswig-Holstein region of Germany; the use of milk replacer was also found to be a risk factor in France [42], and they have been suggested as a potential route of infection in Denmark, where Paisley and Hostrup-Pedersen [50] showed that tallow-based milk replacers could have been responsible for all seven cases of BSE in this country. However, there is no experimental evidence to show that tallow from an infected cow contains infectivity, and so the link between milk replacers and BSE infection remains a hypothesis.…”
Section: Routes Of Infectionmentioning
confidence: 99%
“…A possible causal association between the feeding of potentially contaminated milk replacers to calves and the occurrence of BSE has been suggested by several epidemiologic studies (2)(3)(4)(5). However, no report shows experimental transmission of BSE by use of tallow or milk replacers (6).…”
Section: Milk Replacers and Bovine Spongiform Encephalopathy Inmentioning
confidence: 99%